Strategi Peningkatan Daya Saing Usaha Mikro Tempe Nasabah Lembaga Keuangan Mikro - Arasy Alimudin , Ramadhan Prasetya Wibawa (Universitas PGRI Madiun, 2018)
The problem faced by micro business tempe customer of micro financial institution (LKM) of Sidoarjo Regency so that can improve competitiveness of Micro Business of Tempe for business sustainability is loan interest rate and unstable of soybean price as main raw material of tempe product. The purpose of this study is to examine and determine alternative micro business tempe competitiveness strategy that has obtained financing from MFIs so as to create sustainability of business in the era of MEA competition amid widespread imports of soybeans. The method of research used mix method (mixed method) object of this research is micro entrepreneur of tempe product in village area sepande subdistrict of Sidoarjo district which is not member of cooperative and have become customer of Micro Finance Institution amount 10 person. The analysis method used in this research is SWOT Analysis, SWOT matrix then continued with QSPM (Quantitative Strategic Planning Matrix). The result of the research shows that the right competitiveness strategy is product development strategy by developing the type and variant of tempe product, especially the change of form and packaging which is more interesting and hygienic so that it can give the added value of the product and increase the selling price, which in turn will increase the business profit and can overcome the weaknesses in the burden of interest costs on loans provided by microfinance institutions.